Drivers of digital transformation adoption: A weight and meta-analysis - Cavalcanti, Diego Rodrigues (2022)
Cavalcanti, D. R., Oliveira, T., & Santini, F. D. O. (2022). Drivers of digital transformation adoption: A weight and meta-analysis. Heliyon, 8(2), 1-17. [e08911]. https://doi.org/10.1016/j.heliyon.2022.e08911---Funding: This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia) under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC).